Mergers and acquisitions : ARM takeover by Intel - Custódio, Raul (2012)
By the end of 2009 a lot had already been talked about ARM prospects for the future and its sustainability. Several rumors surfaced that the company could be one of the intervenients in the most interesting deal of the last years among IT companies. Among others, Intel was pointed as the most obvious candidate for the acquisition, however Intel had the company of Google, Apple and Samsung, just to name a few. In this thesis we analyzed the hypothesis of a deal between Intel and ARM, what value would be created for Intel and ARM shareholders, and how much competition would Intel face in the case it decided to move forward. We concluded that the deal is feasible and would create value for Intel and ARM shareholders, at the expense of the current ARM customers and, most likely, final consumers. There seems to be no other firm with capabilities and reasons to go for such deal, and Intel would face no competition, offering a premium of 55% over ARM market value. This would leave value for Intel as we calculated the synergy at 73% the actual ARM market value. Finally as a separated note, it should be kept in mind that such a deal would probably face a tough time being approved by regulators, such is already the dominant position Intel has in the market.